Survey of Aedes sp. Using Ovitrap to Prevent DHF in Beti Ogan Ilir Village - Ramayanti, Indri; Ghiffari, Ahmad; Prameswarie, Thia; Silvana, Rista; Asmalia, Resy; Saputra, Yogi (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service activity aims to provide education and introduce ovitrap to residents of Beti Village, Ogan Ilir Regency so that they can use inexpensive, simple, and safe mosquito traps as one of the efforts to control Dengue Hemorrhagic Fever (DHF). Method: This service consists of counseling knowledge, attitudes, and behaviors about DFH using a pre-test and post-test as measuring tools, as well as making ovitrap skills. Practical Applications: This activity was successful in raising public awareness about the benefits of ovitrap, how to make them, attractants, and how to install them. The results of the ovitrap survey show that Aedes sp. is frequently found in ovitrap installed outside the house. Conclusion: Education to the public has an impact on increasing community awareness and knowledge of DFH prevention. Ovitrap can be used as basic information for the community to improve the clean environment by decreasing mosquito breeding sites.